Induction of Hematopoietic Microchimerism by Gene-Modified BMT Elicits Antigen-Specific B and T Cell Unresponsiveness toward Gene Therapy Products - Martinet, Jérémie; Bourdenet, Gwladys; Meliani, Amine; Jean, Laetitia; Adriouch, Sahil; Cohen, Jose L.; Mingozzi, Federico; Boyer, Olivier (Frontiers in Immunology, 2016)
Background: Gene therapy is a promising treatment option for hemophilia and other protein deficiencies. However, immune responses against the transgene product represent an obstacle to safe and effective gene therapy, urging for the implementation of tolerization strategies. Induction of a hematopoietic chimerism via bone marrow transplantation (BMT) is a potent means for inducing immunological tolerance in solid organ transplantation. Objectives: We reasoned here that the same viral vector could be used firstly to transduce BM cells for inducing chimerism-associated transgene-specific immune tolerance and, secondly, for correcting protein deficiencies by vector-mediated systemic production of the deficient coagulation factor. Methods: Evaluation of strategies to induce B and T cell tolerance was performed using ex vivo gene transfer with lentiviral vectors encoding coagulation factor IX (FIX) or the SIINFEKL epitope of ovalbumin. Following induction of microchimerism via BMT, animals were challenged with in vivo gene transfer with lentiviral vectors. Results: The experimental approach prevented humoral immune response against FIX, resulting in persistence of therapeutic levels of circulating FIX after lentiviral-mediated gene transfer in vivo. In an ovalbumin model, we also demonstrated that this approach effectively tolerized the CD8+ T cell compartment in an antigen-specific manner. Conclusions: These results provide the proof-of-concept that inducing a microchimerism by gene-modified BMT is a powerful tool to provide transgene-specific B and T cell tolerance in a gene therapy setting.